'A Glass Half Full'? Women's history in the UK. Issue 1 (2nd January 2018) - Purvis, June
ABSTRACT: This article offers an overview of the development of women's history in the UK over the last twenty years or so. It is noted that over this period women's history has expanded massively, an expansion that has cut across national boundaries and drawn in scholars from other disciplines than History. Eight themes in women's history are identified as being prominent during this time—a focus on the modern period (post 1780), a strong empirical bent, a questioning of the dominance of a separate spheres discourse, a 'spatial turn', an interest in life stories and biographies, an interest in the women's suffrage movement, a 'religious turn' and a 'transnational turn'. Lastly, consideration is given to the influence of the digital revolution on the development and direction of women's history.